The relationship between belief in a just world and prosocial behavior: the role of psychological resilience and empathic capacity - Liu, Cong; Fan, Wenshu; Tan, Qiuyu; Yun, Kai; Huang, Wei (Frontiers in Psychology, 2025)
ObjectiveThis study investigated how belief in a just world (BJW) influences prosocial behavior tendency (PBT) through psychological resilience (PR), and examined how empathic capacity (EC) moderates this mediation process.MethodData were collected from 955 Chinese university students (Mage = 19.5 years, SD = 1.3; 65.6% female) using validated scales measuring BJW, PBT, PR, and EC.ResultsThree key findings emerged: (1) BJW positively predicted PBT both directly (β = 0.301, p < 0.001) and indirectly through PR; (2) EC moderated the relationship between BJW and PR, with the positive association being stronger for individuals with lower EC (b = 0.45, p < 0.001) compared to those with higher EC (b = 0.23, p < 0.01); (3) The indirect effect of BJW on PBT through PR was stronger for individuals with lower EC, indicating a moderated mediation effect.ConclusionThese findings advance our understanding of prosocial behavior by identifying distinct pathways through which beliefs and emotional capacities interact. The results suggest that interventions to promote prosocial behavior should be tailored based on individual differences in empathic capacity, with different approaches needed for high versus low EC individuals.